2014
DOI: 10.1016/j.neuroimage.2014.07.027
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the relationship between white matter connectivity and creativity

Abstract: Creative cognition emerges from a complex network of interacting brain regions. This study investigated the relationship between the structural organization of the human brain and aspects of creative cognition tapped by divergent thinking tasks. Diffusion weighted imaging (DWI) was used to obtain fiber tracts from 83 segmented cortical regions. This information was represented as a network and metrics of connectivity organization, including connectivity strength, clustering and communication efficiency were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 58 publications
3
48
1
Order By: Relevance
“…The structural neuroimaging study revealed gender differences in the pattern of white mater connectivity between brain regions, particularly within the default mode and cognitive control networks, as a function of creative ability (Ryman et al, 2014). High creativity in females was correlated with lower connectivity and efficiency together with clustering across several brain areas, whereas high creativity among males was associated with greater connectivity and efficiency alongside clustering in fewer brain regions.…”
Section: Gender Creativity and The Brainmentioning
confidence: 99%
See 1 more Smart Citation
“…The structural neuroimaging study revealed gender differences in the pattern of white mater connectivity between brain regions, particularly within the default mode and cognitive control networks, as a function of creative ability (Ryman et al, 2014). High creativity in females was correlated with lower connectivity and efficiency together with clustering across several brain areas, whereas high creativity among males was associated with greater connectivity and efficiency alongside clustering in fewer brain regions.…”
Section: Gender Creativity and The Brainmentioning
confidence: 99%
“…To date, only two EEG studies (Fink & Neubauer, 2006;Razumnikova, 2004), one structural neuroimaging study (Ryman et al, 2014), and one functional neuroimaging study (Abraham, Thybusch, Pieritz, & Hermann, 2014) have been published which specifically addressed the question of gender based brain-related differences in creativity. Fink and Neubauer (2006) found that despite no behavioral differences surfaced between the sexes on the measure of originality, males and females of different verbal ability significantly differed with respect to task-related synchronization of EEG alpha activity in anterior regions of the cortex.…”
Section: Gender Creativity and The Brainmentioning
confidence: 99%
“…Another study showed that during divergent thinking, coupling of the executive control network (the network involved in executive control) and the default mode network is observed. However, a recent study using a larger sample suggested that there are sex differences in the association between white matter structural connectivity and CMDT [Ryman et al, 2014]. The Beaty et al [2015] study also showed that the tendency of "small world" in the network is associated with increased CMDT .…”
Section: Introductionmentioning
confidence: 94%
“…Only a few studies have examined how white matter structural connectivity relates to creative ability (Jung, Grazioplene, Caprihan, Chavez, & Haier, 2010; Jung et al, 2013; Ryman et al, 2014; Takeuchi et al, 2017; Takeuchi et al, 2010, 2011; Wu, Zhong, & Chen, 2016). Takeuchi et al (2010) conducted a diffusion tensor imaging study to examine the relation between white matter integrity (measured with fractional anisotropy) and creative ability.…”
Section: Introductionmentioning
confidence: 99%